How and where satellite cities form around a large city: bifurcation mechanism of a long narrow economy - Ikeda, Kiyohiro (2021)
We investigate economic agglomerations in a long narrow economy, in which discrete locations are evenly spread over a line segment. The bifurcation mechanism of a monocentric city at the center is analyzed analytically to show how and where satellite cities form. This is an important step to elucidate the mechanism of the competition between a large central city and satellite cities, which is taking place worldwide. By the analysis of the Forslid & Ottaviano (J Econ Geo, 2003) model, we show that the larger the agglomeration forces, the farther from the monocentric city satellite cities emerge. As the trade freeness increases from a low value, there occurs a spatial period doubling in which every other city grows. Thereafter a central city with two satellite cities appears, en route to a complete agglomeration to the central city.